145 Preclinical development of EDIT-201, a multiplexed CRISPR-Cas12a gene edited healthy donor derived NK cells demonstrating improved persistence and resistance to the tumor microenvironment. (10th December 2020) - Wong, Karrie; Sexton, Steven; Donahue, Kelly; Antony, Lincy Prem; Wasko, Kevin; Nasser, Jared; Leary, Glenn; Pfautz, Amanda; Porth, Owen; Pierce, William; Sousa, Patricia; Scott, Sean; et al.
Abstract : Background: Natural killer (NK) cells distinguish tumor from healthy tissue via multiple mechanisms, including recognition of stress ligands and loss of MHC class I expression. However, effector function of allogeneic NK cells can be diminished by the lack of functional persistence, as well as tumor-intrinsic immunosuppressive mechanisms, such as production of TGF-β. We developed a next-generation allogeneic NK cell therapy using CRISPR-Cas12a gene editing to enhance NK cell function through knockout of the CISH and TGFBR2 genes. We hypothesized that knockout of CISH, a negative regulator of IL-2/IL-15 signaling, would improve NK cell effector function, while knockout of the TGF-β receptor gene, TGFBR2, would render NK cells resistant to TGF-β mediated suppression. Methods: NK cells were expanded from CD3-PBMC starting material in the presence of 20 ng/mL IL-15 for 14 days. A variety of methods were performed to assess the effects of CRISPR-Cas12a gene editing on primary human NK cells including NGS to assess editing efficiency, flow cytometry, in vitro spheroid killing assays and an in vivo NSG tumor model. These methods were performed consistent with protocols widely accepted in the field. Results: Following editing optimization, we achieved greater than 80% in/dels at both targets in NK cells in both single and double gene knockout (KO, DKO) contexts. Using flow cytometry-based assays we demonstrated that TGFBR2 KO NK cells phosphorylated less SMAD2/3 relative to unedited control NK cells in response to TGF-β, while CISH KO NK cells showed enhanced pSTAT3 and pSTAT5 upon IL-15 stimulation. We next explored the ability of these single knockouts in controlling 3D SK-OV-3 ovarian tumor spheroids and PC-3 prostate tumor spheroids in vitro over 5 days of co-culture. Consistently, both single knockouts demonstrated improved cytotoxicity against tumor targets in the presence of exogenous TGF-β (p<0.0001 for both single KOs). Importantly, in both the SK-OV-3 and PC-3 tumor spheroid killing assays, DKO NK cells demonstrated superior rapid and sustained tumor killing compared to either single knockouts or unedited control NK cells (n=7 independent experiments, 4 unique NK cell donors, p<0.0001), demonstrating additive effects of simultaneously targeting both pathways. Relative to control NK cells, DKO NK cells had increased expression of CD107a, CD25, CD69, and NKp44 after exposure to tumor cells and produced higher concentrations of TNF-a and IFN-g (p<0.01). In an in vivo NSG mouse xenograft model, where SK-OV-3 cells are injected i.p. one week prior to i.p. NK cell infusion, DKO NK cells controlled tumor growth more effectively than unedited NK cells, resulting in lower tumor burden and an increase in median survival time. Conclusions: In summary, using CRISPR-Cas12a we demonstrated highly efficient gene editing of primary human NK cells at two unique targets designed to augment NK cell anti-tumor activity. Together, the increased overall effector function of CISH/TGFBR2 DKO primary human NK cells support their development as a potent allogeneic cell-based medicine for cancer. This potential medicine, termed EDIT-201, is being advanced to clinical study.